IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM MENGENTASKAN KEMISKINAN DI KOTA SAMARINDA - NOVIA ANDRIANI AHNADI; Eny Rochaida; Muliati Muliati (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Novia Andriani Ahnadi, 2019 Program Keluarga Harapan (PKH) is a conditional assistance program that is given to very poor households with the requirements of the health and education component. This program began in 2007 which was later announced as a national program in 2012. In this study the analytical tool used to test is hypothesis testing using the Chi Square method, this method is used to see the effect of PKH to become a government solution in alleviating community poverty through education and health facilities.The results of this study are that there is a very strong relationship between poor household groups with the help of PKH or it can be said that PKH can be a government solution to alleviate community poverty through education and health facilities with sigma exact values is 0.815 then greater than the critical point of 0.05 (0.815 0.05). The implementation of PKH activities on faculties and health facilities from 2010 - 2017 showed a change in the positive attitudes of PKH participants and there was also a decrease in the number of poor people within that year. Where there was a decrease in the level of poor people in Kota Samarinda from 2010 to 2017 there was a decline in the poor population by 18.02%.